A Patient-Controlled Intravenous Analgesia With Tramadol Ameliorates Postpartum Depression in High-Risk Woman After Cesarean Section: A Randomized Controlled Trial - Wu, Zhuoxi; Zhao, Peng; Peng, Jing; Fang, Liang; Ding, Jinping; Yan, Guangming; Wang, Yang; Zhu, Jing; Wang, Dongting; Li, Yang; Chen, Zhengqiong; Zhang, Qingling; et al. (Frontiers in Medicine, 2021)
Abstract Background Postpartum depression (PPD) is a severe psychiatric disorder. Its risk is associated with the cesarean section (CS). Currently, there are few early intervention strategies for these women with PPD who underwent CS. Methods This was a parallel-group randomized controlled trial of singleton pregnant women who underwent elective CS in a tertiary referral hospital in China from October, 2017 to September, 2019. After operation, patients received randomly tramadol patient-controlled intravenous analgesia (PCIA; 4 mg/mL; TRA group), hydromorphone PCIA (0.04 mg/mL; HYD group), or ropivacaine patient-controlled epidural analgesia (PCEA; 1.5 mg/mL; ROP group) for 48 h in a 1:1:1 ratio. Total blinding during hospitalization was not feasible due to differences between the PCEA and PCIA treatments. All investigators who performed the follow-up were blinded to the group assignment. Outcomes A total of 1230 patients were enrolled for eligibility. Intention-to-treat analysis showed reduced incidence of PPD in the TRA group (n=27 [6.6%]) than that in the HYD (10.2%, OR 1.62, 95% CI 0.98~2.68; p=0.059) and ROP groups (10.5%, OR 1.66, 95% CI 1.01~2.75; p=0.046) at four weeks post-operation, however, the difference was not statistically significant (Bonferroni corrected p=0.118, p=0.098, respectively). Subgroup analysis in high-risk women (preoperative Edinburgh Postpartum Depression Scale [EPDS] ≥10) showed a significantly lower incidence of PPD in the TRA group (16.5%) than in the HYD (32.6%) and ROP groups (30.9%) (Bonferroni corrected p=0.022 and p=0.038, respectively). The per-protocol analysis yielded similar results. Reported adverse events (AEs) were mostly mild. None of the women or infant discontinued treatment due to AEs. Conclusions Tramadol PCIA after CS in high-risk women can help to reduce the risk of PPD at four weeks after elective CS.